Evaluation of electrical substation automation operational parameters: A systematic literature review - Mgenge, Mandlenkosi; Swanepoel, Jan Adrian; Muvunzi, Rumbidzai; Daniyan, Ilesanmi Afolabi (Edelweiss Applied Science and Technology, 2024)
The need to address inadequate power supply led to the development of automation strategies to improve the efficiency of power substation. This study conducts a systematic literature on the automation of operational parameters in electrical substation. Initially, 84 articles were retrieved from online as articles and grey literature. Upon the implementation of the inclusion criteria, 31 articles were selected and reviewed due to the fact that their focus and finding match with the aim of this study. The outcome of this study indicates that one of the recent advances in the automation of power substation is the development and implementation of the International Electro-technical Commission (IEC) 61850 standard. The standard boasts of several advantages such high compatibility, interoperability, cyber security features, efficiency, reliability, scalability and centralised control. However, some of its challenges includes time synchronisation standardisation of its testing procedure as well as integration into the communication network architecture. The study may promote the reliability of electrical protection, to reduce load-shedding incidences. It may also assist utilities and other electrical energy industries to better grasp how the automation protocol utilised affects substation efficiency.